Chemical Analysis and Anthelmintic Activity Against Teladorsagia Circumcincta of Nordic Bark Extracts In vitro - Athanasiadou, Spiridoula; Almvik, Marit; Hellström, Jarkko; Madland, Eva; Simic, Nebojsa; Steinshamn, Håvard (Frontiers in Veterinary Science, 2021)
Helminth parasitic infections are common in small ruminants in Norway; infection is usually treated with anthelmintic drugs, but resistance is an increasing problem. It is necessary to identify strategies to reduce the use of anthelmintic drugs and mitigate the impact of anthelmintic resistance. Condensed tannins (CT) rich forages have been shown to reduce the helminth burden in small ruminants, but these forages have limited cultivation potential in Scandinavia. A good source for CT in cold climatic regions may be the bark of several commercially utilized tree species. Here we determined the content and characterized the type of CT in bark extracts of pine (Pinus sylvestris L.), spruce (Picea abies L.) and birch (Betula pubescens). Extracts of selected bark samples were tested for their anthelmintic efficacy against the ovine infectious nematode Teladorsagia circumcincta. Total CT content was higher in the bark from younger (10-40 years old) pine and spruce trees; it decreased with tree age in pine, whereas it remained relatively stable in the bark of spruce and birch. Pine trees consisted of 100% procyanidins, whereas prodelphinins were present in most spruce (4-17%) and all birch samples (5-34%). Our studies have clearly showed that there is variation in the anthelmintic activity of water and acetone extracts of bark samples collected from various sites around Norway, as this was measured with two independent in vitro assays. The anthelmintic activity of some extracts was consistent between the two assays, for example extracts from the 3 samples with the highest CT content, showed very high activity in both assays, whereas the extract from the sample with the lowest CT content showed the lowest activity in both assays. For other extracts, activity was not consistent across the assays, which could be attributed to the susceptibility of the different stages of the parasitic life cycle. We demonstrated that bark extracts from commercially used trees in Scandinavia have the potential to be used as alternatives to anthelmintics. Further work should focus in refining the associations between bark extracts and anthelmintic activity to identify the best strategies to reduce the input of anthelmintic drugs in livestock production systems.